Transcriptomic analysis of resistance and short-term induction response to pyrethroids, in Anopheles coluzzii legs - Kefi, Mary; Charamis, J.; Balabanidou, V.; Ioannidis, P.; Ranson, H.; Ingham, Victoria; Vontas, J. (BMC genomics, 2021)
Insecticide-treated bed nets and indoor residual spraying comprise the major control measures against Anopheles gambiae sl, the dominant vector in sub-Saharan Africa. The primary site of contact with insecticide is through the mosquitoes’ legs, which represents the first barrier insecticides have to bypass to reach their neuronal targets. Proteomic changes and leg cuticle modifications have been associated with insecticide resistance that may reduce the rate of penetration of insecticides. Here, we performed a multiple transcriptomic analyses focusing on An. coluzzii legs.
Gesehen am 04.10.2022